Cyclical and sectoral transitions in the US housing market - Daniel Cooper; Rüdiger Bachmann (Federal Reserve Bank of Boston, 2012)
Using data from the Panel Study of Income Dynamics, this paper examines the flow of U.S. households within and between two distinct segments of the housing market - renter-occupied properties and owner-occupied properties. The paper provides relevant empirical moments for microfounded models of the housing sector. In particular, net flows in the housing market are substantially smaller than the gross flows, as is the case in the literature on labor market flows. Housing market turnover also exhibits substantial heterogeneity in household moving rates, the long-run moving trends, and the cyclical patterns of household moving decisions. Moves by renters tend to lead movements in real GDP, while moves by homeowners are procyclical and/or slightly lag the cycle. The paper further shows that the secular decline in household moves over time is driven by reduced within-sector moves. Taken together, the paper's results imply that models aiming to describe housing market flows will have to feature substantial nonlinearities and/or multiple sector-specific (owner versus renter) shocks.
Keywords: E30; E32; R21; 330; housing market; PSID; turnover; net and gross flows